فقہ حنفی میں اختلاف رائے کی روایت:تجزیاتی مطالعہ(آغازتا۸۰۰ہجری) - Hafiz Muhammad Mushtaq (Pakistan Journal of Islamic Research, 2020)
In Islamic law, there are certain issues that have been decided once and for all. There can be no further discussion or religious ruling on them. However, there are many other additional matters that have not b een clearly decided in the Holy Qurʼān and Sunnah and have instead been left open to critical discussion and interpretation by Islamic scholars and jurists on the basis of consensus. In such matters, it is natural to have different points of view on the same topic by different scholars during critical discussion. Under the same principle, various issues are explained in Hanfi Fiqh or school of thought. In such matters, the opinions of Islamic scholars and jurists are also considered and given weight age, but only after giving precedence to the Holy Qurʼān and Sunnah. However, concrete opinions are given serious consideration in the rest of the matters according to the changing needs and circumstances. This also negates the popular misconception about Hanfi Fiqh that it only promotes blind imitation and copying. On the other hand, fact-based and well-researched opinions are given due importance in the Fiqh Hanfi .There is a long-standing tradition in this Fiqh to have difference of opinion based on the principle of freedom of expression. This tradition is also evolving with the passage of time. All prominent Hanfi jurists have expressed different opinions on certain matters on the basis of their theological research and wisdom. Hanfi Fiqh had started in an environment of tolerance and open discussion and the same tradition still runs strong in this school of thought. This principle started with Imam Abu Hanifa and his disciples and continues to this day in the research of contemporary jurists. However, the present work only focuses on the period between 1st and 10th Hijra.